A Morphometric Analysis of the Digital Bones in Karagouniko Sheep and Hellenic Goat - Theodoros Chatzis; Panagiotis D. Katsoulos; Ioannis Grivas; Aikaterini I. Sideri; Irene Valasi; Aris Pourlis (Ruminants)
The phalanges of Karagouniko ewes and Hellenic goats were the subject of the present quantitative study, with the objective of determining whether any differences existed on the corresponding bones of the different digits. The lengths of the phalanges of the third and fourth digits of the fore and hind autopodia, the smallest diaphyseal breadths of the first and second phalanges, the breadths of the proximal and distal ends of the first and second phalanges, the lengths of the dorsal surfaces of the third phalanx, and the heights of the extensor processes of the third phalanx were measured. A total of 44 linear measurements were recorded for each animal species. The summation of the lengths of the digital bones revealed that the third frontal digit was longer than the fourth frontal digit in both animal species and the fourth hind digit was longer than the third hind digit in both animal species. Furthermore, the lengths of the third and fourth frontal digits were greater than those of the corresponding hind digits in both species. The findings of the current metric analysis suggest that the lengths of the paired digits differ in sheep and goat. The results indicate that the morphometry of the digital bones could be important from phylogenetic, biomechanical, and clinical aspects.